Profile of Brazilian scientific publications on drug interactions in the Intensive Care Unit: a literature review - dos Santos, Jéssica Batista; da Silva , Rafael Lustosa; Cavalcante, Deives Aurélio Melo da Rocha; Benjamini, Luiz Felipe Pohlenz; da Costa, Melina Even Silva; Rodrigues , Fabrícia Tesolin; Lopes , Carlos Eduardo de Araujo; Cabral, Ayara Almeida Souza; Pires, Andreza Lima; da Silva , Bruno Vinícius Pereira (Seven Editora, 2023)
Research Question: What has Nursing published and debated about ICU drug interactions?General and specific objectives respectively: Conduct a survey of articles published in magazines and/or periodicals. To analyze the profile of nursing publications on ICU medication interactions.Hypothesis: There are few nursing publications on drug interactions in the ICU.Type of study: Cross-sectional, descriptive, retrospective, integrative review. DOI: https://doi.org/10.56238/colleinternhealthscienv1-131